Legal Certainty of Online Motorcycle Taxis as Public Transportation in Indonesia - Endro Satoto; Sulhan Sulhan (Yayasan Adra Karima Hubbi, 2024)
Background: Indonesia, as an archipelagic nation, heavily depends on transportation that aligns with its unique geographical conditions. The rapid development of science and technology has transformed the transportation sector, leading to the emergence of alternative modes such as online motorcycle taxis (Ojek online). These services have become a crucial component of road transportation, offering intra-city and inter-city journeys via application-based systems. Objective: This study aims to assess the legal standing of online motorcycle taxis and their alignment with current legislative provisions to determine their status as legitimate public transportation. Methodology: The research adopts a qualitative approach, utilizing legislative reviews, comparative studies, and stakeholder interviews to analyze the regulatory framework governing online motorcycle taxis. Findings: The study reveals that while online motorcycle taxis contribute significantly to the transportation sector, current legislation does not fully recognize them as legitimate public transport providers. This gap affects passenger protection and the certainty of service standards. Conclusion: To ensure safety, reliability, and legal clarity, it is imperative to establish a comprehensive legal framework that formally categorizes online motorcycle taxis as recognized public transportation.